Análisis del cambio de temperatura en Bogotá D.C., los últimos 20 años (2014)
In this paper, an analysis is made of the variation of the maximum, average and minimum monthly temperatures of six stations located in the city of Bogotá D.C, during the periods 1993-2002 and 2003-2012.